Censorship detected in KZ (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Kazakhstan. Data sourced from OONI.
Censorship Incident ID: KZ-2026-0411. Severity: critical. Confidence: 75%